Novel three‐dimensional printing of poly(ester urethane) scaffolds for biomedical applications. (22nd April 2021) - Lores, Nayla J.; Hung, Xavier; Talou, Mariano H.; Abraham, Gustavo A.; Caracciolo, Pablo C.
Abstract: Tissue engineering requires highly porous complex structures with interconnected pores and tightly controlled pore sizes, added to customized production. Additive manufacturing (AM) is nowadays one of the most suitable technologies for the preparation of structures with strictly defined complex three‐dimensional architectures. Moreover, computed tomography and magnetic resonance imaging can be employed to obtain personalized medical devices. Fused deposition modeling (FDM) is one of the most common, easiest, and cost‐effective AM techniques to obtain 3D objects from a wide variety of materials. However, there is a lack of bioresorbable materials that can fit the increasing demand for biomedical applications requiring stiff elastomers. In this work, a series of bioresorbable segmented poly(ester urethanes) (SPEU) with high hard segment content was synthesized and physicochemically characterized. The materials with higher thermal stability were processed into homogeneous filaments by hot‐melt extrusion with no need for additives nor plasticizers. These filaments were evaluated for FDM, and structures with controlled porosity, filament diameter, and in‐plane pore size could be easily obtained by modifying the printing parameters. Regarding SPEU mechanical properties, the obtained scaffolds could be promising for cartilage tissue engineering applications.